-5(x-3)=15(x-7)+2

Simple and best practice solution for -5(x-3)=15(x-7)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-3)=15(x-7)+2 equation:


Simplifying
-5(x + -3) = 15(x + -7) + 2

Reorder the terms:
-5(-3 + x) = 15(x + -7) + 2
(-3 * -5 + x * -5) = 15(x + -7) + 2
(15 + -5x) = 15(x + -7) + 2

Reorder the terms:
15 + -5x = 15(-7 + x) + 2
15 + -5x = (-7 * 15 + x * 15) + 2
15 + -5x = (-105 + 15x) + 2

Reorder the terms:
15 + -5x = -105 + 2 + 15x

Combine like terms: -105 + 2 = -103
15 + -5x = -103 + 15x

Solving
15 + -5x = -103 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
15 + -5x + -15x = -103 + 15x + -15x

Combine like terms: -5x + -15x = -20x
15 + -20x = -103 + 15x + -15x

Combine like terms: 15x + -15x = 0
15 + -20x = -103 + 0
15 + -20x = -103

Add '-15' to each side of the equation.
15 + -15 + -20x = -103 + -15

Combine like terms: 15 + -15 = 0
0 + -20x = -103 + -15
-20x = -103 + -15

Combine like terms: -103 + -15 = -118
-20x = -118

Divide each side by '-20'.
x = 5.9

Simplifying
x = 5.9

See similar equations:

| 1.75x=8 | | 5-(x-3)=6-2x | | 5-x=4x-60 | | 7x-2x=8-3x | | 3x+8=-4x+8 | | -4x-1=-1+7x | | 4x-12=-7x+10 | | 5x-x=3x-2 | | -x+3=23 | | -2x-6=16 | | x^3-12= | | 7x-(3x+6)=5x-47 | | 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 | | x^4-4x^2+12x+9= | | x^4-4x^2+12x+9=0 | | 3x+2.3=5x+1.7 | | (3x-2)(x^2-6x+1)=0 |

Equations solver categories